Particle acceleration and magnetic field amplification in hotspots of FR II galaxies: The case study 4C74.26 - Araudo, A; Bell, A; Blundell, K (Argentinian Astronomical Society, 2016)
It has been suggested that relativistic shocks in extragalactic sources may accelerate the most energetic cosmic rays. However, recent theoretical advances indicating that relativistic shocks are probably unable to accelerate particles to energies much larger than a PeV cast doubt on this. In the present contribution we model the radio to X-ray emission in the southern hotspot of the quasar 4C74.26. The synchrotron radio emission is resolved near the shock with the MERLIN radio-interferometer, and the rapid decay of this emission behind the shock is interpreted as the decay of the downstream magnetic field as expected for small scale turbulence. If our result is confirmed by analyses of other radiogalaxies, it provides firm observational evidence that relativistic shocks at the termination region of powerful jets in FR II radiogalaxies do not accelerate ultra high energy cosmic rays.